2018
DOI: 10.1539/joh.2018-0039-oa
|View full text |Cite
|
Sign up to set email alerts
|

Qualitative and quantitative differences between common occupational health risk assessment models in typical industries

Abstract: Objective: The differences in the methodologies of various occupational health risk assessment (OHRA) models have not been extensively reported. We aimed to understand the qualitative and quantitative differences between common OHRA models in typical industries. Methods: The Environmental Protection Agency (EPA), Australian, Romanian, Singaporean, International Council on Mining and Metals (ICMM), and the Control of Substances Hazardous to Health (COSHH) models were evaluated, and a theoretical framework was e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
22
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 17 publications
3
22
0
2
Order By: Relevance
“…This finding was similar with the result observed by our research team in the previous study that the EPA, COSHH, and Singaporean models were prone to obtain higher risk ratios than the other three models in three industries (ie wooden furniture, electroplating, and crane manufacturing). 21 Some scholars also found similar results. [32][33][34][35][36] They found significant differences of risk levels between different OHRA models in typical industries such as the gas pipeline, electroplating, and chair furniture manufacturing industries.…”
Section: F I G U R Ementioning
confidence: 67%
See 2 more Smart Citations
“…This finding was similar with the result observed by our research team in the previous study that the EPA, COSHH, and Singaporean models were prone to obtain higher risk ratios than the other three models in three industries (ie wooden furniture, electroplating, and crane manufacturing). 21 Some scholars also found similar results. [32][33][34][35][36] They found significant differences of risk levels between different OHRA models in typical industries such as the gas pipeline, electroplating, and chair furniture manufacturing industries.…”
Section: F I G U R Ementioning
confidence: 67%
“…This finding was supported by our preliminary study that reported that the risk ratios of the wood furniture manufacturing, electroplating, and crane manufacturing industries obtained by the EPA, Singaporean, and COSHH models were consistent with the inherent risk of these industries. 21 The possible reasons for the reliability of the three models were that determining the inherent hazard level and the exposure level are relatively objective and accurate, in which determining the inherent hazard of risk factors is usually based on the data from animal experiments or epidemiological investigations, and the determination of exposure level is mainly based on the risk factor's physical and chemical properties, exposure concentration, or exposure time. However, the Australian, ICMM, and Romanian models are mainly based on the professional knowledge and working experience of the assessor when determining the hazard level and assessing the exposure level, which might lead to the subjectivity of the methodology and produce bias.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The risk ratio (RR), 11 which is dened as the ratio between the risk level of a particular nanomaterial (obtained through the given CB tool) and the maximum risk level for that tool, was used for comparing assessment results obtained from different tools. For example, in Nanosafer the risk level of nano-Al 2 O 3 at the separation sampling location is 4, while the maximum risk level for the tool is 5.…”
Section: Air Monitoring For Exposure To Nanomaterialsmentioning
confidence: 99%
“…A multi-criteria qualitative analysis was subsequently established based on this analysis of key information 11,32 and included the following steps: determination of evaluation indicators, assignment of indicator values and weights, expert consultation, interview with key informants, and comprehensive analysis. The evaluation indicators were determined based on the literature review and expert consultation, in which 20 experts in the eld of health management or occupational health were asked for advice on evaluating the indicators in two rounds.…”
Section: The Comparative Study Across Different Cb Toolsmentioning
confidence: 99%